Keeping up with the RALFs: how these small peptides control pollen–pistil interactions in Arabidopsis - Somoza, Sofía Cristina (2021)
The pollen and pistil RALF peptides, along with multiple receptor-like kinases and leucine-rich repeat extensins, regulate pollen tube growth and the final burst within the ovule, where sperm cells are released for fertilisation to occur. This review introduces some new questions that arose about the regulation of this complex process.